2016
DOI: 10.1111/aos.13001
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal membrane surgery evaluated by subjective outcome

Abstract: ABSTRACT.Purpose: To examine pre-and postoperative visual interference, subjective symptoms and visual acuity in patients undergoing epiretinal membrane (ERM) surgery. Methods: A retrospective observational case series comparing 239 eyes in 231 consecutive patients with idiopathic ERM in a selected catchment area from 2002 to 2009. Demography, visual acuity (VA), lens status and subjective symptoms were analysed before and after the operation. Patients, healthy enough to participate at least 2 years post surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In line with previous studies showing a positive association between preoperative and postoperative BCVA, 16,17 our study found that patients with worse preoperative BCVA to have worse postoperative BCVA (P = 0.01, r = 0.32). Studies examining the relationship between preoperative CRT and postoperative visual acuity in patients with idiopathic ERM have yielded mixed results.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies showing a positive association between preoperative and postoperative BCVA, 16,17 our study found that patients with worse preoperative BCVA to have worse postoperative BCVA (P = 0.01, r = 0.32). Studies examining the relationship between preoperative CRT and postoperative visual acuity in patients with idiopathic ERM have yielded mixed results.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, 23G‐ppv with membrane peeling may be regarded as the ‘gold standard’ in therapy for patients with idiopathic ERM, as improvements of VA after surgery through membrane peeling also improve the subjective visual disturbance of patients (Miliatos & Lindgren ). In case of preoperative intraretinal cystoid changes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in visual acuity, with or without metamorphopsia secondary to morphologic distortions of the retinal surface, represents the main indication for ERM surgery 3. Standard surgical treatment consists of pars plana vitrectomy (PPV) and ERM removal resulting in good visual recovery 4…”
Section: Introductionmentioning
confidence: 99%